Integration of Scandinavian genetic data with UK biobank data implicates the RBM20 gene with atrial fibrillation pathogenesis. (14th October 2021) - Vad, O B; Angeli, E; Liss, M; Ahlberg, G; Andreasen, L; Christophersen, I E; Tveit, A; Haunsoe, S; Svendsen, J H; Lundegaard, P R; Gotthardt, M; Olesen, M S
Abstract: Purpose: Atrial fibrillation (AF) is the most common sustained arrhythmia. It carries a large healthcare burden and is associated with serious complications. The arrhythmia has a substantial genetic component and is associated with several structural genes, including the gene TTN. A recent large genome-wide association study on AF found an association to RBM20. The RBM20 gene is a splicing factor targeting TTN, RYR2 and CAMK2D among other cardiac genes. Using Next-Generation Sequencing and data derived from the UK Biobank, we aimed to reveal the role of RBM20 in AF. Methods and results: We examined the burden of rare (Minor allele frequency (MAF)<0.01%) RBM20 loss-of-function (LOF) variants in whole-exome sequencing data from the UK Biobank (n=175, 280). AF was defined by ICD9/10, while individuals without AF were used as controls. Association tests aggregating rare variants in RBM20 using the Efficient Variant-Set Mixed Model Association Test (SMMAT) were performed to assess the effect of LOF RBM20 variants, adjusted for age, sex and principal components. We identified 33 LOF variants in RBM20, which were significantly enriched in AF (P=0.0087). To examine the effect of rare missense RBM20 variants in the splicing of TTN, we screened an in-house cohort of 531 Scandinavian early-onset AF patients using targeted sequencing. We filtered for rare (MAF<0.1%) and deleterious (defined as combined annotation dependent depletion score >20) variants and identified nine missense variants and three novel LOF variants in RBM20. To evaluate the effect of these RBM20 variants, we constructed a series of human RBM20 single nucleotide base exchange mutants. The splicing activity of the variants was measured with RT-qPCR on HEK293 cells transfected with a TTN241–3 splicing reporter. Four of these variants resulted in a significantly altered splicing activity in TTN, with the largest effect observed for LOF variants. In order to examine the biological effect of RBM20 variants on structural changes in atrial tissue, we used a Norwegian Brown rat animal model with loss of RBM20. In this model, Transmission Electron Microscopy revealed altered sarcomere and mitochondrial structure in its atrial cardiomyocytes. Furthermore, nanopore RNA sequencing of atrial tissue from the aforementioned animal model indicated altered expression in several key cardiac genes, including TTN and PITX2. Conclusion: Rare RBM20 LOF variants are significantly enriched in AF cases, seen in a large population of 175, 000 individuals. We demonstrated that the effect of LOF RBM20 on alternative TTN splicing can be detected on an individual level in patients with AF. Studies using an animal model indicates that LOF in RBM20 may affect atrial function through altered expression of several genes in the atria, and may cause structural changes in the atrial cardiomyocytes. This suggests that RBM20 may be involved in AF pathogenesis mediated through an atrial cardiomyopathy. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Novo Nordisk Foundation Pre-Graduate Scholarships (NNF18OC0053094)The Hallas Møller Emerging Investigator grant (Novo Nordisk Foundation (NNF17OC0031204))